A Morphological Analysis of Derivational Affixes in Short Story ”The Ones Who Walk Away From Omelas” by Ursula K. Leguin 1973 - Shandra, Adinda Ayu; Zaim, M. (Universitas Negeri Padang, 2024)
This study aimed identify and examine the derivational affixes present in the short story